Becoming an Antiracist Educator: The Life and Work of Timothy J. Stanley - Ng-A-Fook, Nicholas; Currie, Mark T. S.; Conway, Shannon; Cutrara, Samantha; Gibson, Lindsay; Grant, Nichole E.; den Heyer, Kent; Montgomery, Ken; Farah, Virani-Murji; Nazari, Noorin; Rogers, Pamela; Smith, Bryan; et al. (Université d'Ottawa | University of Ottawa, 2026)
Becoming an Antiracist Educator honours the enduring influence of Timothy J. Stanley, a visionary historian whose work has reshaped how racism, racialization, and historical consciousness are understood in Canada. This timely collection gathers scholars, teachers, and community advocates who reflect on how Stanley’s scholarship and mentorship have challenged and guided their own commitments to antiracist education. Spanning generations and disciplinary backgrounds, the contributors offer deeply personal and politically grounded reflections that connect Stanley’s insights to the pressing realities of our time. They engage questions raised by the toppling of colonial statues, the resurgence of anti-Asian racism, and the uncovering of unmarked graves at residential school sites. Together, they show that antiracist teaching is not only about critiquing systems, but about reimagining how we understand the past, how we tell our histories, and how we live with one another in the present. Concluding with a moving epilogue by Stanley, this collection speaks to educators, researchers, and community members seeking to confront racism in schools, museums, universities, and public life. It offers both a testament to his legacy and an invitation to carry that work forward with courage and care. Becoming an Antiracist Educator is an essential resource for educators, scholars, and community members committed to interrupting racism in schools, museums, universities, and beyond. It offers not only an archive of Stanley’s impact but a roadmap for those seeking to carry his work forward in practical and transformative ways.
Acknowledgements Introduction Toward Becoming an Antiracist Educator Nicholas Ng-A-Fook and Mark T. S. Currie Part I: Shaping Antiracist Approaches Chapter 1 Banalities and Multiplicities: Applying Tim Stanley’s Work in and Across Places Bryan Smith Chapter 2 A Letter to Maleeka: Approaching Inescapable Racializations and Difficult Memories Farah Virani-Murji Chapter 3 Connection Across Space, Time, and Pandemics: A Conversation with Timothy Stanley Samantha Cutrara Chapter 4 Amnesia and Racial Tension: Lessons in the Wake of Racial Reckoning Joseph Smith Chapter 5 “Something to Think About”: Antiracisms and Learning to Kill Canadian History Mark T. S. Currie Part II: “Doing” History Differently Chapter 6 Challenging the Old Guard and Disrupting the Grand Narrative Shannon Conway Chapter 7 The Canadian History Hall Revisited Lindsay Gibson Chapter 8 The Study of Afghan Textbooks for Citizenship Analysis Through the Work of Timothy Stanley Noorin Nazari Chapter 9 Letters, Points, and Trajectories in the Work of Timothy Stanley Kent den Heyer Part III: Mentorship Chapter 10 The Accidental (Not Occidental) Anti‑Essentialist Antiracist Educator Doug Tateishi Chapter 11 Not Just Another Bobby Orr: Reflections on Academic Genealogy and the Scholarship of Timothy J. Stanley Ken Montgomery Chapter 12 “To Affect Eternity by Acting Through Others”: Timothy J. Stanley’s Graduate Student Mentorship Pamela Rogers Chapter 13 “And So?”: Lessons from Timothy Stanley in Engaging Racisms in the World Nichole Grant Epilogue Building Connections: My Humble Reply Timothy J. Stanley References Contributors Index
Keywords: Racisms; Antiracist Education; History Education; Teacher Education; Anti-racist Educator; Racialization; Antiracist; History; Historical consciousness; Colonialism; Residential Schools